Finding a mycorrhizal fungus for reintroductions of the threatened terrestrial orchid Diuris fragrantissima - Smith, Zoe (Universidad de Costa Rica, 2015)
Australian terrestrial orchids rely on associations with suitable mycorrhizal fungi for in situ seed germi- nation and establishment, an important prerequisite for self sustaining populations. Finding an appropri- ate mycorrhizal fungus is therefore imperative to suc- cessful reintroductions. Reintroductions have been planned to conserve the terrestrial orchid Diuris fra- grantissima, which is Critically Endangered in Victoria, Australia, having been reduced to less than 25 plants at a single site.